Synthesis, Antiinflammatory and Antibacterial Activities of Substituted 10H-Indolo[3,2-b]quinoxalines - Thomas Leonard, J.; Rajesh, O.S.; Murugesh, K.; Gunasekaran, V. (Asian Journal of Chemistry, 2016)
A new series of fused quinoxalines as indoloquinoxalines were synthesized by condensing the appropriate isatin and o-phenylenediamine. N-Mannich bases of 10H-indoloquinoxalines (1–9) were synthesized by reacting formaldehyde and various secondary amines with indolo[3,2-b]quinoxaline. These compounds produced good antibacterial and antiinflammatory activities.